Irrigated and non-irrigated cofee (Coffea arabica L.) under super dense conditions - Scalco, Myriane Stella; Alvarenga, Livia Alves; Guimarães, Rubens José; Colombo, Alberto; Assis, Gleice Aparecida (Coffee Science - ISSN 1984-3909, 2012)
This study had the objective to evaluate possible alterations induced by irrigation on a super dense coffee plantation (Coffea arabica L.), with 20 000 plants per hectare, based on values taken along seven consecutive cropping years of green coffee bean yield, bean volume per plant, dry cherry to green coffee bean ratio, and degree of maturation. The experiment was set up on January 2001 at an experimental area of the Universidade Federal de Lavras- MG, with two treatments: (i) drip irrigated plants, and (ii) non-irrigated plants. Whenever the soil water tension, at 0.25m depth reached a value near 60kPa, a drip irrigation system was used to apply the volume of water required to restore field capacity. The highest amount of water used (866mm) was observed during the first harvest year. Observations taken along seven consecutive cropping years indicated that: (i) cherry maturation of drip irrigated coffee plants was delayed in relation to the non-irrigated plants; (ii) the ratio dry cherry to green coffee bean is not affected by irrigation, but dry cherry volume production per irrigated plant was 42% higher than the one produced by non-irrigated plants; (iii) irrigation may provide coffee producers with a 44% increase in coffee bean yield. Besides typical coffee biennial fluctuations of yield, for the 20000 plants ha-1 density, for both irrigated and non-irrigated treatments, no significant observations in decrease in yield along the seven consecutive cropping years was seen.